A survey on the use of metacognitive self-regulatory learning strategies by students from the different faculties of UiTM Pulau Pinang / Rasaya Marimuthu … [et al.] - Marimuthu, Rasaya; Liaw, Shun Chone; Lim, Teck Heng; Er, Ann Nah; Hoe, Foo Terng (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
Self-regulated learning (SRL) is one of the focal points of learner selfdirectedness in any given learning situation, especially in higher learning institutions where learning autonomy is greatly emphasized. Within SRL, it has been discovered that the metacognitive self-regulatory strategies have only been moderately used by students of higher learning institutions. Therefore, this survey was carried out to gauge the level of metacognitive self-regulatory learning strategies employed by the degree students from the different faculties of Universiti Teknologi MARA Pulau Pinang (UiTMPP). The metacognitive self-regulatory strategies subscale from the Motivated Strategies for Learning Questionnaire (MSLQ) by Pintrich, Smith, Gracia and McKeachie (1991) was used for this purpose. It was found that no significant difference existed among the students from the different faculties for the subscale overall. However, some degree of significant difference was discovered for two of the individual items. Additionally, the findings also showed that the majority of the students were only moderate strategy users, besides also highlighting the most commonly used strategies among them, by faculty and overall. The findings of this study could prove useful for course instructors in trying to understand the learning practices of their students, especially the metacognitive strategies and also help to create better learning environments for their students